Revisiting the Growth of Black Phosphorus in Sn-I Assisted Reactions - Wang, Dongya; Yi, Peng; Wang, Lin; Zhang, Lu; Li, Hai; Lu, Min; Xie, Xiaoji; Huang, Ling; Huang, Wei (Frontiers in Chemistry, 2019)
Black phosphorus, an emerging layered material, exhibits promising applications in diverse fields, ranging from electronics to optics. However, controlled synthesis of black phosphorus, particularly its few-layered counterparts, is still challenging, which should be due to the unclear growth mechanisms of black phosphorus. Here, taking the most commonly used Sn-I assisted synthesis of black phosphorus as an example, we propose a growth mechanism of black phosphorus crystals by monitoring the reactions and analysing the as-synthesized products. In the proposed mechanism, Sn24P19.3I8 is the active site for the growth of black phosphorus, and the black phosphorus crystals are formed with the assistance of SnI2, following a polymerization-like process. In addition, we suggest that all Sn-I assisted synthesis of black phosphorus should share the same reaction mechanism despite the differences among Sn-I containing additives. Our results shown here should shed light on the controlled synthesis of black phosphorus and facilitate further applications of black phosphorus.